Hemispheric cerebral blood flow predicts outcome in acute small subcortical infarcts. Issue 10 (October 2021) - Hong, Lan; Ling, Yifeng; Su, Ya; Yang, Lumeng; Lin, Longting; Parsons, Mark; Cheng, Xin; Dong, Qiang
The association between baseline perfusion measures and clinical outcomes in patients with acute small subcortical infarcts (SSIs) has not been studied in detail. Post-processed acute perfusion CT and follow-up diffusion-weighted imaging of 71 patients with SSIs were accurately co-registered. Relative perfusion values were calculated from the perfusion values of the infarct lesion divided by those of the mirrored contralateral area. The association between perfusion measures with clinical outcomes and the interaction with intravenous thrombolysis were studied. Additionally, the perfusion measures for patients having perfusion CT before and after thrombolysis were compared. Higher contralateral hemispheric cerebral blood flow (CBF) was the only independent predictor of an excellent clinical outcome (modified Rankin Scale of 0-1) at 3 months (OR = 1.3, 95% CI 1.1–1.4, P = 0.001) amongst all the perfusion parameters, and had a significant interaction with thrombolysis (P = 0.04). Patients who had perfusion CT after thrombolysis demonstrated a better perfusion profile (relative CBF ≥1) than those who had perfusion CT before thrombolysis (After:45.5%, Before:21.1%, P = 0.03). This study implies that for patients with SSIs, hemispheric CBF is a predictor of clinical outcome and has an influence on the effect of intravenous thrombolysis.